Pendampingan Produksi Pembuatan Siaran Audio (Podcast) Sebagai Perwujudan Katekese Digital Gereja Katolik - Theresia Intan Putri Hartiana; Brigitta Revia Sandy Fista (PeKA: Jurnal Pengabdian Kepada Masyarakat, 2021)
This activity is part of the continuation of research on Media Literacy conducted in 2019. The results of the research show that from each skill in media literacy problems arise at the technical skill level and communicative abilities level. These problems are of course the main focus of this activity, especially regarding participation in content creation to maximize communication abilities through applications. Based on the background of the above problems, Audio Broadcasting Production Assistance (Podcast) was carried out as the embodiment of the Catholic Church's Digital Catechism. This assistance is intended, to provide a new way of packaging the message of tempestuous life for all people. The target object of abdimas is the Catholic Church of Saint Yusup Karanpilang. In the context of communication, the Catholic Church of Saint Joseph, including the late majority. So it is deemed necessary to provide assistance so that the content that is disseminated to the public can be accepted and is good for presentation.